Long-term Tumor Control With Radiotherapy for Symptomatic Hemangioma of a Vertebral Body. Issue 12 (15th June 2019) - Parekh, Akash Dipak; Amdur, Robert J.; Mendenhall, William M.; Morris, Christopher G.; Zlotecki, Robert A.
Abstract : Study Design: Retrospective outcomes review. Objective: To analyze and report long-term outcomes in a cohort of patients treated with radiotherapy (RT) for symptomatic hemangioma of a vertebral body. Summary of Background Data: Data are scarce on the rate of tumor control with long-term (>5 yr) follow-up after RT for symptomatic hemangioma of a vertebral body. Methods: We retrospectively reviewed the medical records of patients treated at our institution between 1971 and 2008 for symptomatic hemangioma of a vertebral body, updated their follow-up, analyzed complications, and calculated the tumor control rate. Tumor control by imaging was defined as no increase in tumor size on computed tomography (CT) or magnetic resonance (MR) scan. Clinical tumor control was defined as no symptoms of recurrent tumor. Results: Ten patients were eligible for analysis. All patients had pain from visible hemangioma at the time of radiotherapy for which surgical resection or interventional radiology procedures were likely to result in high morbidity. Tumors were located in the lumbar (40%), thoracic (50%), or cervical (10%) areas of the spine. The mean radiotherapy dose delivered was 47 Gy. Mean imaging follow-up after completion of radiotherapy was 8.1 years; mean clinical follow-up was 21.2 years. The tumor control rate was 90% (9/10). One patient who may have developed a tumor recurrence had radiographic and clinical evidence of tumor progression 30 years after radiotherapy. The actuarial rate of tumor control was 100% at 5, 10, 20, and 25 years. There was no grade more than or equal to three treatment toxicities, no evidence of malignant transformation, and no evidence of second tumors in treatment area (with the possible exception of the one tumor recurrence). Conclusion: RT for symptomatic hemangioma of the spine provides long-term tumor control with a low risk of serious complications. Radiotherapy is a good option when surgery or an interventional radiology procedure is high-risk. Our preferred dose is 45 Gy at 1.8 Gy/fraction. Level of Evidence: 4 Abstract : We report tumor control after radiotherapy for spine hemangioma in 10 patients treated over 40 years. Local tumor control was 90%. One patient recurred 30 years after radiotherapy. The actuarial rate of tumor control was 100% at 25 years. Radiotherapy for spine hemangioma provides long-term tumor control without complications.